The Phantom of the Opera: Cultural Amenities, Human Capital, and Regional Economic Growth - Oliver Falck; Michael Fritsch; Stephan Heblich (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
We analyze the extent to which endogenous cultural amenities affect the spatial equilibriumshare of high-human-capital employees. To overcome endogeneity, we draw on a quasinaturalexperiment in German history and exploit the exogenous spatial distribution ofbaroque opera houses built as a part of rulers competition for prestigious cultural amenities.Robustness tests confirm our strategy and strengthen the finding that proximity to a baroqueopera house significantly affects the spatial equilibrium share of high-human-capitalemployees. Then, a cross-region growth regression shows that these employees induce localknowledge spillovers and shift a location to a higher growth path.
Keywords: H41; J24; R11; 330; Cultural Amenities; Regional Economic Growth; Human Capital; Bohemians; Musikwirtschaft; Kultursektor; Infrastruktur; Wohnstandort; Hochqualifizierte Arbeitskräfte; Spillover-Effekt; Regionales Wachstum; Schätzung; Deutschland